Three Essays on Insider Trading Profitability, Uncertainty Disclosure Tone, Carbon Performance and Customer Concentration - Geng, Hongshan (Curtin University, 2025)
The thesis comprises three essays on insider trading profitability in US listed firms. The essays examine the relationship between insider trading profit, uncertainty disclosure tone, carbon emission performances and customer concentration level of the firm. How insider trading profit is affected by non-financial elements is discussed. Insider trading profit as a representative of a firm’s internal management level has discussed whether it has relationship to the carbon emission performances.